Improving Teacher Competence in Blended Learning-Based Technology from a Gender Perspective - Halimatussakdiah Halimatussakdiah; Alfi Julizun Azwar; Eka Sartika (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
This study is motivated by the increasing demand for teachers’ technological competence in blended learning after the COVID-19 pandemic, as well as the persistent gender disparities in access to and use of educational technology. The objective of this research is to analyze efforts to improve teachers’ competence in technology-based blended learning from a gender perspective. The study employs a mixed-method approach, combining quantitative surveys and qualitative interviews involving teachers from various educational levels. The survey measures teachers’ technological competence, while interviews explore their experiences, challenges, and access to training. The results reveal significant differences in competence influenced by gender, age, and teaching experience. Male teachers generally demonstrate higher confidence and better access to technology training, whereas female teachers, particularly in rural areas, face limitations related to time, resources, and socio-cultural factors. These disparities affect the effectiveness of blended learning implementation. The study highlights the need for gender-responsive and flexible training programs to ensure equal opportunities for all teachers. This research contributes by offering a gender-based framework to enhance teacher competence, support inclusive professional development, and promote equitable and effective learning environments in the digital era.